SARS‐CoV‐2 infection and early mortality of waitlisted and solid organ transplant recipients in England: A national cohort study. Issue 11 (16th September 2020) - Ravanan, Rommel; Callaghan, Chris J.; Mumford, Lisa; Ushiro-Lumb, Ines; Thorburn, Douglas; Casey, John; Friend, Peter; Parameshwar, Jayan; Currie, Ian; Burnapp, Lisa; Baker, Richard; Dudley, Jan; et al.
Abstract : Patients waitlisted for and recipients of solid organ transplants (SOT) are perceived to have a higher risk of contracting severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) and death; however, definitive epidemiological evidence is lacking. In a comprehensive national cohort study enabled by linkage of the UK transplant registry and Public Health England and NHS Digital Tracing services, we examined the incidence of laboratory‐confirmed SARS‐CoV‐2 infection and subsequent mortality in patients on the active waiting list for a deceased donor SOT and recipients with a functioning SOT as of February 1, 2020 with follow‐up to May 20, 2020. Univariate and multivariable techniques were used to compare differences between groups and to control for case‐mix. One hundred ninety‐seven (3.8%) of the 5184 waitlisted patients and 597 (1.3%) of the 46 789 SOT recipients tested positive for SARS‐CoV‐2. Mortality after testing positive for SARS‐CoV‐2 was 10.2% (20/197) for waitlisted patients and 25.8% (154/597) for SOT recipients. Increasing recipient age was the only variable independently associated with death after positive SARS‐CoV‐2 test. Of the 1004 transplants performed in 2020, 41 (4.1%) recipients have tested positive for SARS‐CoV‐2 with 8 (0.8%) deaths reported by May 20. These data provide evidence to support decisions on the risks and benefits of SOT during the coronavirus disease 2019 pandemic. Abstract : The authors link national datasets in England and compare waitlisted patients and transplant recipients on the incidence of SARS‐CoV‐2 infection and subsequent mortality to inform risk/benefit decisions during the COVID‐19 pandemic.